Psychometric properties of the Hindi version of Geriatric depression scale (HGDS) - jee, S.Gopal (IJRDO-Journal of Applied Science, 2016)
The present study reports the Hindi version of the Geriatric depression scale (GDS) and its psychometric properties. The Hindi version of the GDS was developed following the contemporary methodology of cross-cultural adaptation of psychometric tools. The Geriatric depression scale, The Brief Assessment Schedule Depression Cards (BASDEC) and Mini Mental Status Examination were administered on a sample of 176 elderly in the age range of 60 to 90 years. The data were analyzed and tested on the basis of traditional test theory. The cross language equivalence of Hindi version of GDS was ascertained by back translation method. Findings revealed a satisfactory subscale to total correlation as well as satisfactory reliability (Internal consistency assessed by Chrobach’s alpha was 0.74). For ascertaining the convergent validity coefficient of HGDS, two criterion measure such as Brief assessment schedule card (BASDEC) and Hindi version of Mini Mental Status Examination (HMMS) were taken and found to be significant correlation between them. The findings suggest that the HGDS is a reliable and valid tool for evaluation of depression in elderly population. The HGDS provide a quick assessment of depression in elderly person and total score of this test reflects the gloomy mood in geriatric population.